Peran Strategis Industri Asuransi terhadap Pencapaian Sustainable Development Goals (SDGs): Peluang, Tantangan, dan Implikasi Kebijakan Publik: Indonesia - Haposan Bakara (Jurnal Deliberatif, 2026)
The achievement of the Sustainable Development Goals (SDGs) requires the active participation of various stakeholders, including the financial services sector. As one of the key institutions in risk management, the insurance industry plays a strategic role in supporting sustainable development through financial protection, risk mitigation, and long-term investment mobilization. This study aims to analyze the strategic role of the insurance industry in achieving the SDGs, identify the opportunities and challenges faced by the industry, and examine the public policy implications necessary to strengthen its contribution to sustainable development. This research employs a qualitative approach using a literature review method by analyzing academic publications, policy documents, regulations, and relevant reports related to insurance, sustainable development, and public policy. The findings indicate that the insurance industry contributes significantly to several SDGs, particularly those related to poverty reduction, health, economic growth, sustainable infrastructure, and climate action. However, the industry faces various challenges, including low insurance penetration, limited sustainable insurance products, regulatory constraints, human resource capacity gaps, and increasing environmental risks due to climate change. Therefore, strengthening regulatory frameworks, enhancing insurance literacy, developing sustainable insurance products, and integrating environmental, social, and governance (ESG) principles into insurance business practices are essential to optimize the industry's contribution to sustainable development. The study concludes that the insurance industry has substantial potential to become a strategic partner in achieving the SDGs, provided that comprehensive public policy support and stakeholder collaboration are effectively implemented.